Bifunctional 64Cu-labelled macrobicyclic cage amine isothiocyanates for immuno-positron emission tomography. Issue 11 (29th October 2014) - Paterson, Brett M.; Buncic, Gojko; McInnes, Lachlan E.; Roselt, Peter; Cullinane, Carleen; Binns, David S.; Jeffery, Charmaine M.; Price, Roger I.; Hicks, Rodney J.; Donnelly, Paul S.
Abstract : Sarcophagine ligands with isothiocyanate functional groups were conjugated to trastuzumab, radiolabelled with 64 Cu and used to image HER2-positive tumours using PET. Abstract : New macrobicyclic cage amine or "sarcophagine" (sar) bifunctional chelators have been synthesised that form copper complexes of exceptional in vivo stability and incorporate isothiocyanate (-NCS) functional groups for conjugation to an antibody. The chelators were synthesised from the methyl-capped complex [Mg II (CH3 )(NH2 )sar] 2+ . Coordination of Mg II within the cavity of the cage amine ligand protects the secondary amine atoms from reacting with the -NCS functional groups. Two different [Mg II (NCS-sar)] 2+ derivatives were conjugated to the HER2/neu-targeting antibody trastuzumab and the progress of the reaction monitored by electrospray mass spectrometry. The Mg II ion was removed from the immunoconjugates under mild conditions (0.1 M citrate buffer, pH 6). Labelling of the (CH3 )( p -NCS-Ph)sar-trastuzumab conjugate with 64 Cu II, a radioisotope suitable for positron emission tomography (PET), was fast (∼5 min) and easily performed at room temperature with high radiochemical purity (>95%). Biodistribution and PET imaging studies in vivo showed that 64 Cu-labelled (CH3 )( p -NCS-Ph)sar-trastuzumab maintained high stability under physiological conditions with high and selective uptake in a HER2-positive cancer cell line. The stability of the copper complex and the 12.7 h half-life of the radioisotope allows clear visualisation of tumours out to 48 h.